Specialization of Tourist Offering by Modeling a Package Tour for Gambling Tourism - Ianeva, Mariana; Gaydarov, Nikola (Research Papers, 2019)
The importance of the issues subject of this study is determined by the fact that Bulgarian tourism is looking for new forms of diversification of the tourism.The aim of the article is to explore and prove basic steps that correspond to the achieved contributions (results), such as:analysis of good practices in casino tourism;methodological framework for research of specialized sites for gambling tourism identified through determined criteria and evaluation indicators;modeling of a specialized gambling product of an Inbound Tour Operator (ITO) based on survey results.In order to achieve the objectives and tasks the following research methods have also been used:Overview of theoretical research;Review of materials from international and European organizations;Review of company surveys;Empirical research.Other contributions (results): The model is aimed at assisting the work of tourist managers in identifying and improving the parameters in the selection of suppliers as well as the implementation of good practices in the package tour.At present, the possibilities for diversification of the product offering of the tour operators are not sufficiently explored in Bulgaria, according to the basic and complementary specialization of the tourist regions and the opportunities for development of all-year-round forms of tourism.JEL: L83, L21, O26
Keywords: Experience economy; Specialized tourist product; Casino tourism; Bundled product of a tour operator